Проблемы оценки стоимости малого предприятия - Иоселева, К. Ю. (ХНУРЭ, 2015)
Background research is determined by the fact that in current conditions worsened the problem of "survival" of the enterprises due to increased competition, especially in those areas where there is a high variability of the technological and organizational conditions for doing business, particularly - in infocommunications.
Keywords: стоимость малого предприятия; оценка стоимости предприятия; малое предприятие